Implementation of Indonesian state fiscal policy during the early period of the pandemic - Sahara, Radi; Dadi Kuswandi; Rini Dwiastutiningsih; Sri Wulan Ratih (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The spread of the Covid-19 virus is challenging for the government from the economic side. This is because various economic activities have slowed down or even stopped entirely so that, as a result, economic movement is significantly reduced. This led to the need for the government to adjust its various policies, including fiscal policy. This study aims to see how the government's policies in Indonesia regarding fiscal policy at the beginning of the pandemic. This research will be carried out using a qualitative approach. The data obtained came from various research results and previous studies. This study found that the government adjusts the state's fiscal policy in receiving and issuing state revenues. In terms of revenue, the government focuses on corporate income tax and corporate income tax as the primary source of state revenue. As for the expenditure side, the government focuses on realizing the use of funds so that the results are right on target. Both of these are done to maintain economic stability in Indonesia.